Людина у сучасному світі швидких змін і трансформацій - Тішко, Лілія Володимирівна; Tishko, Liliya (Leadership and innovation university, 2023)
У статті досліджуються особливості адаптивності людей ХХІ ст. Акцентується увага на нагальній необхідності володіння цією характеристикою кожним індивідом для нормального співіснування з іншими членами суспільства та задоволення власних потреб. The article explores the peculiarities of adaptability of people of the XXI century. The attention is focused on the urgent need for each individual to possess this characteristic for normal coexistence with other members of society and satisfaction of their own needs.
A Person In The Modern World Rapid Changes And Transformations
Keywords: адаптивність; adaptability; суспільство; society; інформаційна епоха; information age; трансформація; transformation, мислення; thinking